Ecological and Economic Problems of Environmental Security - Mashchenko Maryna A. (Bìznes Inform, 2018)
The article is aimed at defining a common mechanism for assessing the ecological and economic threats and ecological losses on the basis of a long-term study to ensure the environmental security of the State. The necessity of a new approach to the State regulation through achievement of environmental security is displayed, that will allow to reduce tensions of the ecological-economic problems in Ukraine. For implementation of this approach, a general mechanism for estimation of ecological-economic threats and ecological losses is provided, which is carried out through formation of an integral costs system. The costs system is presented in the article in the form of an in-depth mechanism for estimating the ecological-economic threats on the example of ecological impacts. Structuring and preparation of the costs system for applied researches is the next stage of this prolonged research.